Cross-Layer Combining of Adaptive Modulation and Truncated ARQ in Multichannel Beamforming MIMO Systems - Ivanis, Predrag; Drajic, Dejan; Brkic, Srdan (Společnost pro radioelektronické inženýrství, 2015)
In this study the authors provide a cross-layer design of multiple-input-multiple-output (MIMO) systems, with the aim to maximize spectral efficiency. We consider MIMO systems based on a multichannel beamforming technique that combines an adaptive modulation and truncated automatic repeat request procedures, for the case of Rayleigh fading propagation and imperfect channel state information. Closed-form expressions for the average spectral efficiency and the packet loss rate are derived for arbitrary eigenchannel of multichannel beamforming systems, with any number of receiving and transmitting antennas. An analytical expression for the average time during which a particular constellation is used continuously, is also derived. We propose the method based on the optimization of the target packet error rate and the maximum number of retransmissions that outperforms the existing cross-layer combining procedures. Furthermore, we develop the numerical algorithm for optimization of the eigenchannel power allocation. The proposed cross-layer design results in higher average spectral efficiency, reduced maximum delay and increased energy efficiency. The analytical results are validated by Monte Carlo simulation.
Keywords: Adaptive modulation; automatic repeat request; crosslayer design; MIMO systems; Rayleigh channels